How can population‐based studies best be utilized to reduce the global impact of dementia? Recommendations for researchers, funders, and policymakers. Issue 10 (23rd June 2020) - Stephan, Blossom C. M.; Siervo, Mario; Brayne, Carol
Abstract: In the last two decades, there has been in‐depth investigation into understanding the pathogenesis, epidemiological profiling, and clinical characterization of dementia. However, these investigations have not led to successful interventions to prevent, delay, or reverse the pathological processes underlying dementia. Recent findings of a decrease in dementia risk in high‐income countries such as the UK, USA and the Netherlands highlight that dementia, at least in some cases, is preventable. This article includes a synthesis of current knowledge on dementia epidemiology, biological underpinnings, risk factors, and current prevention programs, with the aim to set the path for research, funding, and policy initiatives to address the global public health challenge of how to prevent dementia or reduce risk within the framework of population‐based studies. We advocate for development of novel approaches for intelligent data synthesis that go well beyond single approaches to enable powerful risk stratification analyses. An integrated approach is needed where researchers, funders, policymakers, and stakeholders contribute to and work together to formulate effective strategies for the global monitoring and development of population‐based risk reduction, treatment, and prevention programs for dementia.